Exploring oral health related awareness, perceptions, practices and experiences among type 2 diabetes mellitus patients: a mixed method design - Aymen Elsous; Aesha Fetaiha; Mahmoud Radwan (BMC Oral Health)
Abstract Background/Objective The World Health Organization has classified diabetes mellitus as a pandemic disease, which is causing it to become a major worldwide health concern. It can have significant long-term repercussions, especially on dental health, if treatment is not received. The study aimed to explore patients with type 2 diabetes, awareness to, perceptions to and practices regarding oral health, in addition to their experiences. Materials and methods Convergent triangulation was applied from May to November 2022. 376 patients with type 2 diabetes mellitus participated in the quantitative part and 13 patients involved in the qualitative study. The quantitative study was applied in five randomly selected primary health centers representing the five Gaza governorates using self-developed semi-structured questionnaire. The qualitative study was applied in two central primary health centers. Descriptive analysis was applied using the SPSS software and thematic analysis was approached for the qualitative study. Results 64.4% of patients see themselves susceptible to oral health problems, and 67.8% perceived severity of oral complications of diabetes mellitus. Moreover, 73.2% perceived benefits from oral health practices and 56.2% perceived barriers to oral health practices. Patients' awareness regarding oral health complications from DM and oral health practices are inadequate (57.6%), as well as oral health habits (42.5%). Main themes elucidated from the qualitative study are dental care service quality, patient-dentist interaction, oral hygiene and self-care, and the patient's experiences with oral health problems. Conclusions The results point to important gaps in patients' knowledge and attitudes about dental health in relation to diabetes mellitus. Even though most people are aware of their vulnerability to oral health problems and the seriousness of any potential consequences, a sizable portion continue to believe that there are obstacles in the way of good oral hygiene habits. Poor oral hygiene practices and a lack of knowledge about oral health issues point to the need for more focused interventions and improved educational programs. The significance of high-quality dental care services, productive patient-dentist relationships, and encouraging self-care behaviors are all emphasized by the qualitative findings. In order to improve patient outcomes and encourage better dental hygiene habits among diabetics, these issues must be addressed. This will ultimately reduce oral health complications and increase general well-being.